2010
DOI: 10.1080/07315724.2010.10719818
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Index, Dietary Glycemic Load, and Incidence of Heart Failure Events: A Prospective Study of Middle-Aged and Elderly Women

Abstract: Objective Dietary glycemic index (GI) and glycemic load (GL), measures of the propensity of dietary carbohydrate to increase blood glucose, have been associated with risk of coronary heart disease, but their association with incidence of heart failure (HF) is unknown. We therefore assessed whether dietary GI and GL were associated with rates of HF events. Methods We conducted a prospective, observational study of 36,019 women 48-83 years old without baseline HF, diabetes, or myocardial infarction who were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Several prospective studies assessing the relationship between dietary GI or GL and cardiovascular disease risk were identified ( Table 9 ). Those reporting on cardiovascular disease mortality [ 77 , 78 ] or on incident cardiovascular diseases (all combined) [ 79 , 80 ], coronary heart disease [ 81 , 82 , 83 , 84 , 85 ], stroke [ 80 , 82 , 85 ], myocardial infarction [ 80 , 86 ], or heart failure [ 87 ] were included herein. Most studies provided risk estimates that were adjusted for dietary factors, age, body mass index, and other potentially confounding factors.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
“…Several prospective studies assessing the relationship between dietary GI or GL and cardiovascular disease risk were identified ( Table 9 ). Those reporting on cardiovascular disease mortality [ 77 , 78 ] or on incident cardiovascular diseases (all combined) [ 79 , 80 ], coronary heart disease [ 81 , 82 , 83 , 84 , 85 ], stroke [ 80 , 82 , 85 ], myocardial infarction [ 80 , 86 ], or heart failure [ 87 ] were included herein. Most studies provided risk estimates that were adjusted for dietary factors, age, body mass index, and other potentially confounding factors.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
“…No association was found between the estimated GI or GL of the diet and risk for type 2 diabetes (45), ischemic cardiovascular disease (46) or heart failure (55). Out of the three studies on MI, one study did not find an association (47), one study reported a positive association only among obese or physically inactive individuals (56), and the third study reported a lower risk of MI if replacing saturated fatty acids with low GI food instead of high GI food on equal percentage of energy basis (48).…”
Section: Glycemic Indexmentioning
confidence: 99%
“…A recent epidemiological study found that hospitalization or death from new onset heart failure was not related to sugar intake over a 9 year follow-up in middle age and elderly women [6]. There is less information regarding effects of sugar intake in populations that are at high risk for developing heart failure, such as patients with hypertension, ischemic heart disease or inherited cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%